Evaluating the Quality of Al-'Ashri Arabic Textbooks for Class XI: A Comprehensive Assessment - Hidayah, Uridul; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative research aims to assess the quality of the Al-'Ashri Arabic textbooks designed for class XI. Employing descriptive methods, the primary data source is the Al-'Ashri Arabic textbook itself, while secondary sources include relevant academic literature. The sample consists of language teachers, and data is collected through a questionnaire. The study reveals commendable scores across various aspects, with an average percentage of 89.43%. This indicates that the Al-'Ashri Arabic textbook for class XI demonstrates a high level of quality and effectiveness in its content. This research offers valuable insights for educators and curriculum developers in the field of Arabic language education. Highlight: Comprehensive Evaluation: This research provides a comprehensive evaluation of the Al-'Ashri Arabic textbooks, encompassing various aspects, offering a holistic perspective on their quality. Educator Guidance: The study offers valuable guidance to educators and curriculum developers in the field of Arabic language education, aiding them in making informed decisions about instructional materials. Quantitative Analysis: Employing quantitative methods and data analysis, this research brings an objective and data-driven approach to textbook assessment, enhancing its credibility and applicability. Keyword: Arabic Textbook Evaluation, Quality Assessment, Curriculum Development, Language Education, Educational Effectiveness